Pengaruh Influencer, Financial Technology dan Perencanaan Keuangan terhadap Keputusan Investasi Investor Muda di Pasar Modal Syariah - Wahyuni Sri Rezeki; Supardi Mursalin; Kustin Hartini (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2026)
This study aims to examine the influence of influencers, financial technology, and financial planning on the investment decisions of young investors in the Islamic capital market, both partially and simultaneously. This research employs a quantitative approach with a causal associative research design. The population of this study consists of sharia stock investors registered with KISI Securities at STIA Bengkulu, with a sample of 50 respondents selected using purposive sampling techniques. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS version 18. The results show that, partially, influencers do not have a positive and significant effect on the investment decisions of young investors in the Islamic capital market. Meanwhile, financial technology and financial planning have a positive and significant effect on investment decisions. Simultaneously, influencers, financial technology, and financial planning have a significant effect on investment decisions. This study indicates that the investment decisions of young investors are more influenced by technological factors and financial planning capabilities rather than social influence from influencers. Keywords: Influencers, Financial Technology, Financial Planning, Investment Decisions, Islamic Capital Market.